Role of Intracoronary Imaging in Acute Coronary Syndromes - Gregory Petrossian; Denizhan Ozdemir; Keyvan Karimi Galougahi; Jonathan Scheiner; Susan V Thomas; Richard Shlofmitz; Evan Shlofmitz; Allen Jeremias; Ziad A Ali (US Cardiology Review)
Intravascular imaging with optical coherence tomography (OCT) and intravascular ultrasound provides superior visualization of the culprit plaques for acute coronary syndromes (ACS) compared with coronary angiography. Combined with angiography, intravascular imaging can be used to instigate ‘precision therapy’ for ACS. Post-mortem histopathology identified atherothrombosis at the exposed surface of a ruptured fibrous cap as the main cause of ACS. Further histopathological studies identified intact fibrous caps and calcified nodules as other culprit lesions for ACS. These plaque types were subsequently also identified on intravascular imaging, particularly with the high-resolution OCT. The less-common non-atherothrombotic causes of ACS are coronary artery spasm, coronary artery dissection, and coronary embolism. In this review, the authors provide an overview of clinical studies using intravascular imaging with OCT in the diagnosis and management of ACS.